ANALISIS FINANSIAL USAHATANI KEDELAI DAN NILAI TAMBAH TAHU DI KABUPATEN LOMBOK TENGAH - Shafina Nabilah; Lukman Mohammad Baga; Netti Tinaprilla (Universitas Sebelas Maret, 2015)
The objectives of this research are to analyze the financial of soybean farmingand count the number of value added processing tofu in Central Lombok Regency. The research was conducted in Pujut Sub-district in Central Lombok and taken 30 farmers as the sample. The sample are soybean farmer which selected by purposive sampling. The result showed that soybean farming is feasible to develop because R/C > 1. The ratio of value added tofu is 44.8 percent of the production value.